Transferência de gestão dos projetos habitacionais do Estado para “entidades sem fins lucrativos”: entre a autogestão e o neoliberalismo - Wanderley, Leonardo Fiusa (2013)
This study consists of an attempt to understand the processes of management transfers of housing projects for "nonprofit organizations", based on the inquiry as its instrumentality to the neoliberal offensive in Brazil and also regarding the possibility of strengthening the historical workers’ struggles for self-management. Therefore, it became necessary to investigate some of neoliberalism workings and its influence on housing policy in Brazil and, on the other hand, search for self-management’s concept and the contours of its emergence in the fight for housing. Besides seeking how management transfers of housing policy are part of the set of macrostructures changes engendered by the neoliberal offensive and of the context of the workers’ struggles history, was also sought to grasp how this tension is materialized in a real case. The public selection No. 001/2010 of Bahia State Government and the housing project developed from this study at Girau Grande and Tabatinga, in Maragogipe-Ba, were used as sources. The analysis of the experience showed points of affinity and estrangement with both perspectives and also expanded the perceptions of the contradictions involving the object of work.